STUDI KITAB RIJAL AL-HADIS - Fikri, Shofil; Azzahra, Fatimah; Khanifah, Halimatus; Hariri, Ahmad Nizar; Aulia, Muhammad Restu (STIT Darul Hijrah Martapura, 2024)
This study discusses the book Rijal al-Hadith which is very important in the study of Hadith science. This field deals with individuals connected in the chain of transmission (sanad), namely the narrators of Hadith. Rijal al-Hadith talks about the narrators of Hadith, aimed at assessing the validity of Hadith from the perspective of the chain of narration, whether the connections are sound or flawed by any narrator. This research focuses on how al-Mizzi obtained or revealed narrators in a valid manner. The author also seeks this information. Therefore, the author hopes to contribute to broader and more specific research on the book Rijal al-Hadith.